Three-year mortality rate of suicide attempters in consultation-liaison service. (1st October 2016) - Chen, Hong-Ming; Hung, Tai-Hsin; Chou, Shih-Yong; Tsai, Ching-Shu; Su, Jian-An
Abstract: Objective: Suicide attempters might be sent to the emergency room for urgent medical intervention. Some with more severe physical morbidity may be hospitalised, and psychiatrists might be consulted for suicide evaluation. The aim of our study was to investigate the three-year all-cause mortality rate of hospitalised suicide attempters with regard to the effect of consultation-liaison services, and to identify any risk factors associated with mortality. Methods: Between 2002 and 2006, 196 inpatients from medical or surgical wards in a general hospital who had consulted psychiatrists because of suicide attempts were collected consecutively. We traced their mortality incidence during a three-year period, and calculated the mortality rate and time (days) to death. Results: Three-year all-cause mortality was 20.4%, and there was a higher risk of mortality in the first two years after the index suicide attempt. In the adjusted Cox regression model, associated risks included male gender, older age, diagnosis of depressive disorders and lack of psychiatric follow-up. Conclusions: We found that hospitalised suicide attempters had higher all-cause mortality after discharge, and determined that psychiatric follow-up is helpful. More attention should be paid to those with potential risk factors, and timely intervention is suggested in order to reduce mortality.